No nukes in Africa : South Africa, the denuclearisation of Africa and the Pelindaba Treaty (Historia, 2021)
African efforts to denuclearise Africa originated in the 1960s in response to French nuclear tests in the Sahara Desert and to apartheid South Africa's nuclear weapons programme. The Organisation of African Unity joined the UN in the mid-1960s to denuclearise the continent. With international opposition to its apartheid policies, the South African government became increasingly isolated; a situation which worsened as confirmation of the country's nuclear capabilities revealed the extent of its nuclear weapons programme. By the end of the 1980s, the apartheid government under President F.W. de Klerk decided to terminate the South African nuclear weapons programme as well as its apartheid policies; a decision which accelerated the denuclearisation of Africa. Once South Africa's commitment to nuclear non-proliferation became evident, the continent included it in negotiations on an African Nuclear Weapons Free Zone Treaty (Pelindaba Treaty). With the treaty's entry into force in July 2009 and South Africa's subsequent election to leadership positions in the treatyâ??s compliance mechanism, South Africa's nuclear diplomacy with Africa entered a new phase which continues to pose challenges to the continent's commitment to nuclear non-proliferation.  Pogings om Afrika van kernwapens te vrywaar het hul oorsprong in die sestiger jare as 'n reaksie teen Frankryk se kern toetse in die Saharawoestyn en apartheid Suid-Afrika se kernwapen program. Die Organisasie vir Afrika-eenheid het in die middel sestigerjare by die Verenigde Nasies aangesluit om kernwapens uit Afrika te verwyder. Internasionale teenkanting teen apartheid het daartoe gelei dat die Suid-Afrikaanse regering toenemend geïsoleer is. Hierdie toestand is vererger namate die omvang van die land se kernwapen program bekend geword het. Teen die einde van die tagtiger jare het die apartheids regering onder leiding van President F.W. de Klerk besluit om die Suid-Afrkaanse kernwapen program te staak en om apartheid af te skaf. Hierdie besluite het die kernontwapening van Afrika versnel. Namate Suid-Afrika se toewyding tot kernontwapening duideliker geword het, is die land by onderhandelinge oor 'n verdrag oor 'n kernwapenvryesone in Afrika betrek. Die verdrag het in Julie 2009 in werking getree met Suid-Afrka as verkose leier van die verdrag se nakomings meganisme. Hiermee het die land se kern diplomasie 'n nuwe fase betree. Hierdie fase bide nuwe uitdagings vir kern nie-proliferasie op die kontinent.
Keywords: Afrika; Pelindaba Treaty; Nuclear weapon free zone; Organisation of African Unity; Diplomacy; Pelindaba-verdag, Afrika-unie; Diplomasie; Kernwapenvryesone; Suid-Afrika; South Africa; Africa; Organisasie vir Afrika-eenheid; African Union